Investigation of guided wave propagation and attenuation in pipe buried in sand. (7th July 2015) - Leinov, Eli; Lowe, Michael J.S.; Cawley, Peter
Abstract: Long-range guided wave testing is a well-established method for detection of corrosion defects in pipelines. The method is currently used routinely for above ground pipelines in a variety of industries, e.g. petrochemical and energy. When the method is applied to pipes buried in soil, test ranges tend to be significantly compromised and unpredictable due to attenuation of the guided wave resulting from energy leakage into the embedding soil. The attenuation characteristics of guided wave propagation in an 8 in. pipe buried in sand are investigated using a laboratory full-scale experimental rig and model predictions. We report measurements of attenuation of the T (0, 1) and L (0, 2) guided wave modes over a range of sand conditions, including loose, compacted, mechanically compacted, water saturated and drained. Attenuation values are found to be in the range of 1.65–5.5 dB/m and 0.98–3.2 dB/m for the torsional and longitudinal modes, respectively, over the frequency of 11–34 kHz. The application of overburden pressure modifies the compaction of the sand and increases the attenuation. Mechanical compaction of the sand yields similar attenuation values to those obtained with applied overburden pressure. The attenuation decreases in the fully water-saturated sand, and increases in drained sand to values comparable with those obtained for compacted sand. Attenuation measurements are compared with Disperse software model predictions and confirm that the attenuation phenomenon in buried pipes is essentially governed by the bulk shear velocity in the sand. The attenuation behaviour of the torsional guided wave mode is found not to be captured by a uniform soil model; comparison with predictions obtained with the Disperse software suggest that this is likely to be due to a layer of sand adhering to the surface of the pipe.